2018
DOI: 10.3389/fphys.2018.00428
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of Kir7.1 Inwardly Rectifying K+ Channel Probed in a Knock-in Mouse Expressing a Haemagglutinin-Tagged Protein

Abstract: Kir7.1 encoded by the Kcnj13 gene in the mouse is an inwardly rectifying K+ channel present in epithelia where it shares membrane localization with the Na+/K+-pump. Further investigations of the localisation and function of Kir7.1 would benefit from the availability of a knockout mouse, but perinatal mortality attributed to cleft palate in the neonate has thwarted this research. To facilitate localisation studies we now use CRISPR/Cas9 technology to generate a knock-in mouse, the Kir7.1-HA that expresses the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
10
1
Order By: Relevance
“…Within tissues where Kir7.1 is highly expressed, large variations in glycosylation have been recently observed using a knockin mouse expressing an HA-tagged Kir7.1 channel (38). Notably, the study showed predominantly immature forms of the channel in the lung, whereas full complex glycosylation was observed in the trachea (38). No explanation for variation in glycosylation patterns between these two tissues was given, but our data may suggest a possible mechanism by which such changes could occur.…”
Section: Gpcrs Differentially Regulate Kir71 Glycosylationmentioning
confidence: 50%
See 1 more Smart Citation
“…Within tissues where Kir7.1 is highly expressed, large variations in glycosylation have been recently observed using a knockin mouse expressing an HA-tagged Kir7.1 channel (38). Notably, the study showed predominantly immature forms of the channel in the lung, whereas full complex glycosylation was observed in the trachea (38). No explanation for variation in glycosylation patterns between these two tissues was given, but our data may suggest a possible mechanism by which such changes could occur.…”
Section: Gpcrs Differentially Regulate Kir71 Glycosylationmentioning
confidence: 50%
“…The data shown here provide evidence for molecular regulation of Kir7.1 structure and function by GPCRs. Within tissues where Kir7.1 is highly expressed, large variations in glycosylation have been recently observed using a knockin mouse expressing an HA-tagged Kir7.1 channel (38). Notably, the study showed predominantly immature forms of the channel in the lung, whereas full complex glycosylation was observed in the trachea (38).…”
Section: Gpcrs Differentially Regulate Kir71 Glycosylationmentioning
confidence: 86%
“…Key features of β-catenin GOF in the CP include dysregulation of factors that are essential for the CP to produce the CSF. These include several anion cation exchangers, ion channels, and solute transporters each of which acts as regulators of CSF composition: a sodium-potassium ATPase, Atp1a1 (Ernst et al, 1986); an epithelial sodium channel, Scnn1a (Amin et al, 2009); an inward rectifying potassium channel, Kcnj13 (Cornejo et al, 2018); a voltage-gated potassium channel, Kcna1 (Speake et al, 2003); and a sodium-potassium-chloride cotransporter 1, Nkcc1 , that modulates water transport underlying CSF production (Steffensen et al, 2018) and is also associated with Blood CSF barrier disruption (Kim & Jung., 2012). Furthermore, the expression of several genes encoding transporters for glucose, chloride, and amino acids, is also downregulated in the β-catenin GOF CP.…”
Section: Discussionmentioning
confidence: 99%
“…HEK‐293 cells seeded in 6‐well plates were transfected with 1 μg of plasmid DNA for WT Kir7.1‐HA (2 μg for the case of the concatemer) (Cornejo et al . 2018) or mutants thereof (2 μg for the case of the concatemer) using Lipofectamine 3000. After 24 h the cells were biotinylated with 1 mg ml −1 of sulfo‐NHS‐SS‐biotin twice for 20 min each time on ice.…”
Section: Methodsmentioning
confidence: 99%
“…Fig. 2B shows an experiment using WT Kir7.1 where a large current (in red) present at the onset of the pulse decays slowly to a value that corresponds to patch leak as inhibition by Ba 2+ takes place (Shimura et al 2001;Cornejo et al 2018). The difference between the initial current and that at the end of the pulse is defined as the specific Kir7.1-mediated current.…”
Section: Modifying Kir71-r162c With Methylthiosulfonate (Mts) Reagentsmentioning
confidence: 99%